2011
DOI: 10.1111/j.1601-6343.2011.01520.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of testosterone on craniosynostotic calvarial cells: a test of the gene/environmental model of craniofacial anomalies

Abstract: Testosterone exposure caused an increase in cell proliferation for CS osteoblast cells. However, a therapy targeted to mitigate this response (flutamide therapy) similarly affected CS and WT cells, suggesting that the administration of flutamide or TP in the presence of flutamide decreases osteogenesis of these cells. Thus, although our data support a mechanism of gene-environmental interaction, these results would not support a therapeutic intervention based on this interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The aberrant proliferation of suture-derived cells that has been shown to contribute greatly to craniosynostosis [ 14 ], we then investigated the ability of periostin to modulate the proliferation of the suture-derived cells. As determined by CCK-8, a colorimetric assay used to measure cell viability and cytotoxicity, periostin significantly inhibited the proliferation of suture-derived cells in concentration- and time-dependent manners as compared with the non-treated group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The aberrant proliferation of suture-derived cells that has been shown to contribute greatly to craniosynostosis [ 14 ], we then investigated the ability of periostin to modulate the proliferation of the suture-derived cells. As determined by CCK-8, a colorimetric assay used to measure cell viability and cytotoxicity, periostin significantly inhibited the proliferation of suture-derived cells in concentration- and time-dependent manners as compared with the non-treated group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is noteworthy due to the 3x higher incidence of this phenotype in male patients compared to female patients in our study ( Table 1 ). Dysregulation of androgen hormones has previously been implicated in both syndromic and non-syndromic cases of craniosynostosis [ 52 ] and the androgen receptor is abundantly expressed within the dura matter and calvarial bones of fetal mice [ 53 ]. Increased androgen hormones can also affect expression of TGF-beta, leading to increased osteoblast differentiation and premature suture fusion [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased androgen hormones can also affect expression of TGF-beta, leading to increased osteoblast differentiation and premature suture fusion [ 54 ]. Multiple studies of suture closure in rabbits have indicated that treatment with the androgen-blocker flutamide can delay suture fusion and cause increased sutural separation [ 52 , 54 ]. In vitro treatment of fetal murine dural and osteoblast cells with androgen hormone 5-alpha dihydrotestosterone, has also been demonstrated to increase differentiation and proliferation, supporting androgen involvement in suture fusion [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…As most cases of craniosynostosis are non-syndromic with no identified genetic mutation efforts are now focusing on the association of potential mediators on calvarial growth and development and synostosis [ 51 , 52 ]. SSRI use (exposure to fetus through blood/placental barrier) has been identified as having an elevated risk association for craniosynostosis [ 1 , 2 , 4 , 5 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%